High precision measurement of muonium hyperfine structure. (November 2018) - Tanaka, T; Abe, M; Aoki, M; Fukao, M; Iinuma, H; Ikedo, Y; Ishida, K; Ito, T U; Iwasaki, M; Kadono, R; Kamigaito, O; Kanda, S; et al.
Abstract: MuSEUM (Muonium Spectroscopy Experiment Using Microwave) collaboration aims to measure the muonium hyperfine structure (MuHFS, vhfs ) with a few ppb (parts per billion). MuHFS spectroscopy is a stringent test of the bound-state QED. From this measurement, the muon-proton magnetic moment ratio ( μμ / μ P ) and the muon-electron mass ratio ( mμ / me ) can also be determined by applying a high magnetic field. In the previous MuHFS measurement carried out at Los Alamos Meson Physics Facility (LAMPF), the main uncertainty was caused by the lack of the statistics. MuSEUM collaboration uses the high intense pulsed muon beam at Japan Proton Accelerator Research Complex (J-PARC) to improve the statistical uncertainty. We are also developing our own experimental setups for the improvement of the systematic uncertainties. From June 2016, MuSEUM collaboration have carried out the MuHFS measurement in an extremely low magnetic field within 100 nT and now we are preparing for the measurement in a 1.7 T high magnetic field.